Real-time optimization and control of 3DOF helicopter system via extremum seeking algorithm - Ra'afat, Safanah M.; Ali, Shahad S.; Akmeliawati, Rini (IEEE, 2015)
In this paper, a real-time optimized PropotionalIntegral-Derivative (PID) controller for a three Degree of Freedom (3DOF) helicopter is proposed. The real-time optimization of the PID controller gains is performed by the extremum seeking algorithm. The system is an under-actuated mechanical system with high nonlinearity and high coupling among its states. Such system is affected by the outside disturbances which may affect the stability of the system and lead to instability. For these reasons, an advanced controller that is capable of tuning the controller gains adaptively to the sudden changes, has the ability of regulation and finding best tracking performance is required. The Extremum Seeking (ES) control is a paradigm that aims to find an extremum value of an unknown nonlinear mapping. Therefore, it will be useful to apply ESC to tune PID controller. Experimental results demonstrate that the tracking errors of elevation and pitch angles are converged to the vicinity of the desired operating points with high robustness